Comparative transcriptomics reveal differential gene expression among Plasmodium vivax geographical isolates and implications on erythrocyte invasion mechanisms. - Daniel Kepple; Colby T Ford; Jonathan Williams; Beka Abagero; Shaoyu Li; Jean Popovici; Delenasaw Yewhalaw; Eugenia Lo (Public Library of Science (PLoS), 2024)
The documentation of Plasmodium vivax malaria across Africa especially in regions where Duffy negatives are dominant suggests possibly alternative erythrocyte invasion mechanisms. While the transcriptomes of the Southeast Asian and South American P. vivax are well documented, the gene expression profile of P. vivax in Africa is unclear. In this study, we examined the expression of 4,404 gene transcripts belong to 12 functional groups and 43 erythrocyte binding gene candidates in Ethiopian isolates and compared them with the Cambodian and Brazilian P. vivax transcriptomes. Overall, there were 10-26% differences in the gene expression profile amongst geographical isolates, with the Ethiopian and Cambodian P. vivax being most similar. Majority of the gene transcripts involved in protein transportation, housekeeping, and host interaction were highly transcribed in the Ethiopian isolates. Members of the reticulocyte binding protein PvRBP2a and PvRBP3 expressed six-fold higher than Duffy binding protein PvDBP1 and 60-fold higher than PvEBP/DBP2 in the Ethiopian isolates. Other genes including PvMSP3.8, PvMSP3.9, PvTRAG2, PvTRAG14, and PvTRAG22 also showed relatively high expression. Differential expression patterns were observed among geographical isolates, e.g., PvDBP1 and PvEBP/DBP2 were highly expressed in the Cambodian but not the Brazilian and Ethiopian isolates, whereas PvRBP2a and PvRBP2b showed higher expression in the Ethiopian and Cambodian than the Brazilian isolates. Compared to Pvs25, gametocyte genes including PvAP2-G, PvGAP (female gametocytes), and Pvs47 (male gametocytes) were highly expressed across geographical samples.